Структура и семантика адресата в цикле Б. Кенжеева Послания. Монреаль 1889 - Saule Abiszewa (Polilog: Studia Neofilologiczne, 2013)
Structure and semantics of the addressee in B. Kenzheyev’s cycle Messages. Montreal 1889